SOURCES AND FLUIDS IN THE MANTLE WEDGE BELOW KAMCHATKA, EVIDENCE FROM ACROSS-ARC GEOCHEMICAL VARIATION - Churikova T.; Dorendorf F.; Wörner G. (My University, 2001)
Major and trace element and Sr Nd Pb isotopic variations ill mafic volcanic rocks hve been studied in a 220 km transect across the Kamchatka are from the Eastern Volcanic Front, over the Central Kamchatka Depression to the Sredinny Ridge in the back-arc. Thirteen volcanoes and lava fields, from 110 to 400 km above the subducted slab, were sampled. This allows its to characterize spatial variations and the relative amount and composition of the slab fluid involved in magma genesis. Typical Kamchatka arc basalts, normalized for fractionation to 6% MgO. display a strong increase in large ion lithophile, light rare earth and high field strength elements from the arc front to the back-arc. Ba/Zr and Ce/Pb ratios, however, are nearly constant across the arc, which suggests a similar fluid input for Ba and Pb. La/Yb and Nb/Zr- increase from the are front to the back-arc. Rocks from the, Central Kamchatka Depression range in Sr-87/Sr-86 from 0.70334 to 0.70366, but have almost constant Nd isotopic compositions (Nd-141/Nd-144 0.51307-0.51312). This correlates with the highest U/Th ratios in these rocks. Pb-isotopic ratios are mid-ocean ridge basalt (MORB)-like but decrease slightly from the volcanic front to the back-mv. The initial mantle source ranged from N-MORB-like ill the volcanic front and Central Kamchatka Depression to more enriched in the back-arc. This enriched component is similar to all ocean-island basalt (OM) source. Variations in (CaO)(6.0)-(Na2O)(6.0) show that degree of melting decreases fi-om the arc front to the Central Kamchatka Depression and remains constant from there to the Sredinny Ridge. Calculated fluid compositions have a similar trace element pattern across the arc, although minor differences are implied. A model is prevented that quantifies the various mantle components (variably depleted, N-MORB-mantle and enriched OIB-mantle) and the fluid compositions added to this mantle wedge. The amount of fluid added ranges from 0.7 to 2.1%. The degree of melting changes from similar to 20% at the arc front to < 10% below the back-an, region. 77if, xocksfioni volcanoes qj'thc northern part of the Central Kamchatka Depression to the north of the transect considered in this study - are significantly, different in their trace element composition) compared with the other rocks of the transect and their source appear) to have been enriched by a component derived from melting of the edge of the ruptured slab.
Keywords: geochemical zonation; Kamchatka; subduction zone; mantle sources; ﬂuid